Path Analysis on Factors Affecting Job Performance of Midwives at Community Health Centers in Mojokerto, East Java - Veterina Rizki Amalia; Hanung Prasetya; Bhisma Murti (Journal of Health Policy and Management, 2021)
Background: Midwives play an important role in reducing maternal and neonatal morbidity and mortality. The performance of midwives is an important indicator to improve the quality of maternal and child health services. The purpose of this study was to analyze the factors that affect the performance of midwives.Subjects and Method: This cross-sectional study was conducted at a community health center in Mojokerto, East Java, from February to April 2020. A sample of 200 midwives was selected by random sampling. The dependent variable was the performance of the midwife. The independent variables were age, income, workload, work motivation, perceived financial compensation, education, employment status, social support, and marital status. The performance of midwives was measured by the 6-DSNP. Other data were collected using a questionnaire. Data were analyzed by path analysis using the Stata 13 application.Results:The performance of midwives increased with age ≥ 42 years (b= 3.19; 95% CI= 1.62 to 4.75; p <0.001), family income ≥ 7 million (b= 3.03; 95% CI= 1.50 to 4.56; p <0.001 ), light workload (b= 2.66; 95% CI= 1.19 to 4.13; p <0.001), strong work motivation (b = 3.32; 95% CI= 1.60 to 5.04; p <0.001), sufficient perceived financial compensation (b = 3.96; 95% CI= 1.68 to 4.99; p <0.001). The performance of midwives was indirectly affected by education, employment status, social support and marital status.Conclusion: Age, family income, workload, work motivation, and perceived financial compensation affect the performance of midwives.Keywords: performance, midwives, path analysisCorrespondence: Veterina Rizki Amalia. Masters Program in Public Health, Universitas Sebelas Maret.Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: veterinarizki1@gmail.com. Mobile: +6281359016501.Journal of Health Policy and Management (2021), 06(01): 21-34https://doi.org/10.26911/thejhpm.2021.06.01.03